A survey of incentive mechanisms in static and mobile P2P systems. (December 2015) - Haddi, Fatima Lamia; Benchaïba, Mahfoud
Abstract: Peer-to-Peer (P2P) systems suffer from several forms of non-contribution which depend on possible collaborative operations of a peer. Since peers are usually driven by their self-interest at the expense of social welfare, incentive mechanisms motivate peers to collaborate to simultaneously achieve self-utility and social welfare. Multiple incentive mechanisms have been developed to enhance collaboration. In this paper, we draw up the objectives and the roles of incentive mechanisms. We also describe collaboration according to system and application types. Finally, we present a classification of incentive mechanisms according to the underlay and the incentive scheme.